2020
DOI: 10.1108/ijccsm-06-2020-0073
|View full text |Cite
|
Sign up to set email alerts
|

Research on grassland ecosystem service value in China under climate change based on meta-analysis: a case study of Qinghai province

Abstract: Purpose Grassland in Qinghai as the main type of ecosystem in this region is located in arid and semi-arid areas. The ecosystem is fragile and sensitive to climate change. Grassland ecosystem not only provides essential ecological and life functions for human society but also plays a vital role in mitigating and adapting to climate change. The empirical literature on grassland ecosystem services value (ESV) does not consider the impact of climate change and regional economic development level factors, which pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…These grasslands provide diverse ecosystem services with multiple regulating, provisioning and cultural services, which contributes to their higher ecosystem service value (Boval et al, 2017). Previous studies on grassland economic value or that employed meta‐analysis focused more on ecosystem services, without paying much attention to different grassland types (Huber & Finger, 2020; B. Kang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These grasslands provide diverse ecosystem services with multiple regulating, provisioning and cultural services, which contributes to their higher ecosystem service value (Boval et al, 2017). Previous studies on grassland economic value or that employed meta‐analysis focused more on ecosystem services, without paying much attention to different grassland types (Huber & Finger, 2020; B. Kang et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Huber and Finger (2020) undertook a meta‐analysis focusing on the recreation service of grasslands with samples from European countries. B. Kang et al (2020) reported meta‐regression results on grassland ecosystem service values considering valuation methods based only on observations from Qinghai Province in China. The meta‐analysis conducted by Ren et al (2016) reported the monetary value changes of grassland biodiversity services before and after restoration in China.…”
Section: Introductionmentioning
confidence: 99%
“…4.1 The impact of climate change, environmental pollution and conservation variables on the water ESV is significant and worthy of attention Climate change, environmental pollution and conservation variables are the focus of this paper. Relevant scholars have analyzed the impact of different climatic conditions on the value of ecosystem services such as forests, cultivated land, and grasslands (Nelson et al, 2013;Li et al, 2016;Siriwardena et al, 2016;Gollany and Venterea, 2018;Scheiter et al, 2019;Balasubramanian, 2019;Kang et al, 2020). This paper believes that it is particularly important to study the impact of climatic conditions on the value of water ecosystem services.…”
Section: Discussionmentioning
confidence: 99%
“…This study provides an assessment for the survival prediction of cloned plants under nitrogen deposition related to climate change and has important theoretical and practical significance for the sustainable management of grassland ecosystem in arid and semi-arid regions. Kang et al (2020) revealed a positive correlation between grassland ecosystem service value and climate factors. Compared with the annual average precipitation, the annual average temperature was found to have a more significant impact on ecosystem service value.…”
mentioning
confidence: 95%